Efficient zinc/cobalt inter-replacement in northeast Pacific diatoms and relationship to high surface dissolved Co : Zn ratios - Kellogg, M.M.; McIlvin, M.R.; Vedamati, J.; Twining, B.S.; Moffett, J.W.; Marchetti, A.; Moran, D.M.; Saito, M.A. (Wiley Blackwell, 2020)
The importance of zinc (Zn) as a nutrient and its ability to be substituted for by cobalt (Co) have been characterized in model marine diatoms. However, the extent to which this substitution capability is distributed among diatom taxa is unknown. Zn/Co metabolic substitution was assayed in four diatom species as measured by the effect of free ion concentrations of Zn2+ and Co2+ on specific growth rate. Analysis of growth responses found substitution of these metals can occur within the northwest Atlantic isolate Thalassiosira pseudonana CCMP1335, the northeast Atlantic isolate Phaeodactylum tricornutum CCMP632, and within the northeast Pacific isolates Pseudo-nitzschia delicatissima UNC1205 and Thalassiosira sp. UNC1203. Metabolic substitution of Co in place of Zn in the Atlantic diatoms supports their growth in media lacking added Zn, but at the cost of reduced growth rates. In contrast, highly efficient Zn/Co substitution that supported growth even in media lacking added Zn was observed in the northeast Pacific diatoms. We also present new data from the northeast Pacific Line P transect that revealed dissolved Co and Zn ratios (dCo : dZn) as high as 3.52 : 1 at surface (0–100 m) depths. We posit that the enhanced ability of the NE Pacific diatoms to grow using Co is an adaptation to these high surface dCo : dZn ratios. Particulate metal data and single-cell metal quotas also suggest a high Zn demand in diatoms that may be partially compensated for by Co.